SISTEM PEMELIHARAAN BARANG TEMUAN: Studi Terhadap KUH Perdata dan Hukum Islam - MAHFUDHAN, MAHFUDHAN (State Islamic University (UIN) Ar-Raniry, 2016)
The regulations on found property are still very obscure within the Indonesian laws as the legal protection in this republican state. To this date, the regulations have no significant contribution to the improvement of the laws. This research on the found property maintenance was aimed at finding out the answer to the basic problems and the output from the theory of the found property, as well as the important basis of the standard rules on the found property, especially in the Indonesian laws. Findings showed that the Civil Code assessed the rights and obligations regarding the found property obtained by the status levels of the objects. On the other hand, in the Islamic law, the main concern was on the right to control and the right to have the objects. In essence, the purpose was to protect a person's rights. This indication could be seen from the Islam’s ways by not distinguishing the identity of the property (i.e. beneficial or not, big or small, valuable or not) and also by paying attention to the status of the person who had found and owned it, as well as the right to control or to be recognized legally for the status of the object in question.